Nightmares with the Bible: the good book and cinematic demons - Wiggins, Steve A. (Nomos Verlagsgesellschaft mbH & Co. KG, 2020)
Demons! Nightmares with the Bible views demons through two lenses: that of western religion and that of cinema. Sketching out the long fear of demons in western history, including the Bible, Steve A. Wiggins moves on to analyze how popular movies inform our beliefs about demonic forces. Beginning with the idea of possession, he explores the portrayal of demons from ancient Mesopotamia and the biblical world (including in select extra-biblical texts), and then examines the portrayal of demons in popular horror franchises The Conjuring, The Amityville Horror, and Paranormal Activity. In the final chapter, Wiggins looks at movies that followed The Exorcist and offers new perspectives for viewing possession and exorcism. Written in non-technical language, this book is intended for anyone interested in how demons are perceived and how popular culture informs those perceptions.